Versorgungsprozesse von Patienten mit Verdacht auf Sepsis in einer deutschen Notaufnahme - Geier, F.; Greve, Y.; Popp, S.; Achterberg, A.; Gloeckner, E.; Ziegler, R.; Heppner, Hans Jürgen; Mang, Harald; Christ, Michael (Deutsche Medizinische Wochenschrift, 2014)
Background: The in-hospital mortality of patients with severe sepsis and septic shock (ssss) is high. Of note, little is known about the health care situation of patients with sepsis in German emergency departments. The aim of the study was to analyze whether sepsis patients are treated according to current guidelines, to identify the treatment sites within the hospital and to evaluate the death rate of affected patients during index hospitalization. Patients and methods: In this single-centre, prospective and observational trial we analyzed consecutive patients with complaints of sepsis during August and September 2012. Results: During the study period 151 patients presented with complaints of sepsis (age 68.3 ± 18 years, 54.3 % men, 45 % with ssss, in-hospital mortality of the overall cohort: 14.6 %). The Surviving Sepsis Campaign three hour bundle (lactate, blood cultures, broad spectrum antibiotics, and volume) was carried out in 54.2 % of patients with ssss. In case of ssss, broad spectrum antibiotics were initiated in the emergency department in 85.4 %. Patients with ssss were admitted to wards with usual care in 67.2 %, in 32.8 % they were admitted to an intensive or intermediate care unit. The in-hospital mortality of patients with ssss during their index hospitalization was 27.8 %. Conclusion: Despite the high in-hospital mortality rate, more than two thirds of the patients with ssss were admitted to wards with usual care. We call for action 1) to early identify affected patients, 2) to provide adequate risk stratification tools and 3) to realize an early disposition of patients to the appropriate care units.
CRIS-Team Scopus Importer:2022-09-26
Keywords: disposition; emergency department; guideline-based health care; in-hospital mortality; sepsis